PROPORSI MANGGA PODANG-PISANG KEPOK DAN KONSENTRASI JERUK NIPIS TERHADAP KARAKTERISTIK FRUIT LEATHER MANGGA - Rejeki, Fungki Sri; Anggita, Della; Wedowati, Endang Retno (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Fruit leather is a snack product from puree of fruit look like thin sheeted with a thickness of 2-3mm, easily formed texture, and canâ??t broken when rolled. The raw material used was an extract of podang manggo. The fruit leather texture is influenced by pectin, acid, and sugar, so the addition of kepok banana puree is needed as a source of pectin, and lime juice to reduce pH on mixed puree. The research used Randomized Block Design with 2 factors and repeated 3 times. The first factor was the comparison of podang manggo extract and white kepok banana puree (90%:10%; 80%:20%; 70%:30%). The second factor was a concentration of lime juice (0%; 0,4%; 0,8%).Parametersobserved were yield, pH, moisture content, crude fiber content, reducing sugar content, and organoleptic including aroma, flavor, and texture. The result showed that the best treatment was 80% podang manggo extract, 20% white kepok banana puree, and 0,4% lime juice which fruit leather with characteristics yield 25,5%, pH value 4,2, water content 30,81%, crude fiber content 1,51%, reducing sugar content 55,97%, and the percentage of organoleptic scores of aroma 31,1%, taste 56,6%, and texture 47,7%.